Claus tail gas hydrogenation catalyst as well as preparation method and application thereof
By adding low-temperature active components and antioxidants to the Klaus exhaust hydrogenation catalyst, a catalyst with multifunctional catalytic performance and high antioxidant capacity was prepared, which solved the problem that existing catalysts could not have both multifunctionality, and achieved efficient treatment of the exhaust gas of the sulfur recovery device, meeting national emission standards.
Patent Information
- Application Number
- CN202311238838.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2043-09-22
AI Technical Summary
The existing Klaus exhaust hydrogenation catalyst cannot have the multifunctional functions of catalyzing sulfur dioxide hydrogenation, organic sulfur hydrolysis and CO transformation, and its antioxidant capacity is insufficient and cannot meet the current national emission standards.
By adding low-temperature active components and antioxidants, a Klaus exhaust hydrogenation catalyst with aluminum-titanium-silicon-based composite support and rare earth metal oxides as active components is prepared to improve its low-temperature catalytic activity and antioxidant ability.
It has achieved the versatility of catalytic sulfur dioxide hydrogenation, organic sulfur hydrolysis and CO transformation, significantly improved the antioxidant capacity of the catalyst, can meet the current national environmental protection emission standards, and is suitable for sulfur recovery devices in the petroleum refining and coal chemical industries.
Smart Images

Figure CN119680526A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sulfur recovery, and in particular to a Claus tail gas hydrogenation catalyst, a preparation method thereof, and its application in sulfur recovery tail gas treatment, in particular in the treatment of acid gas with high CO2 content. Background Art
[0002] Sulfur recovery refers to the conversion of sulfides in toxic sulfur-containing gases (acid gases) such as hydrogen sulfide into elemental sulfur. Sulfur recovery usually adopts the Claus sulfur production process, which is industrially carried out through two steps: high-temperature thermal reaction in the sulfur production furnace and low-temperature catalytic reaction in the converter. Due to the limitations of the thermodynamic equilibrium and reversible reaction of the Claus process, the conversion rate cannot be high enough, so that Claus tail gas usually contains a small amount of hydrogen sulfide and other sulfur-containing compounds, such as sulfur dioxide, carbon disulfide, carbonyl sulfide and Sx. Direct incineration cannot meet the current national tail gas emission standards, so it is necessary to remove hydrogen sulfide and sulfur-containing compounds before that.
[0003] Claus tail gas is treated by hydrogenation reactor, sulfur dioxide is hydrogenated and reduced, and organic sulfur is hydrolyzed into hydrogen sulfide. This process requires efficient tail gas treatment special hydrogenation catalyst. The gas passing through the hydrogenation reactor selectively absorbs hydrogen sulfide through solvent. After treatment, the sulfur content is extremely low and can be burned and released into the atmosphere. However, in the acid gas entering the sulfur recovery unit, the CO2 content in some acid gas is too high. For example, the CO2 content in the acid gas of the low-temperature methanol washing unit of Sinopec Qilu Branch is as high as 80%. In the acid gas reactor, CO2 can be reduced to CO by hydrogen sulfide and sulfur, which makes the CO content in Claus tail gas high. If it is not treated, the CO content of the tail gas finally burned and discharged into the atmosphere is too high and cannot meet the current national emission standards. Excessive CO2 content in acid gas will also lead to an increase in the organic sulfur content in Claus tail gas. The Claus tail gas entering the hydrogenation reactor also contains some oxygen. Therefore, it is necessary to develop a Claus tail gas hydrogenation catalyst with high low-temperature activity and strong antioxidant ability, which has the function of efficiently catalyzing sulfur dioxide hydrogenation, organic sulfur hydrolysis and CO conversion, which is of great significance for the sulfur recovery unit to achieve SO2 and CO emission standards.
[0004] A Chinese patent application with publication number CN100591418C discloses a method for preparing a tail gas hydrogenation catalyst for a Claus sulfur recovery unit. The catalyst is a nickel-based catalyst prepared by a coprecipitation method, wherein the main active component is nickel oxide, with a content of 20.1%-60%, and the auxiliary active components are any one, any two or any three of chromium oxide, copper oxide and magnesium oxide, with a content of 0%-10%, and the rest is aluminum oxide. Although the catalyst has good low-temperature activity, it has poor antioxidant ability and does not have the function of catalyzing CO conversion.
[0005] A Chinese patent application with publication number CN101879451A discloses a method for preparing a low-temperature Claus tail gas hydrogenation catalyst. The catalyst carrier is made of silicon-modified aluminum-titanium-silicon composite dry glue, a binder, a pore expander and an additive. The active component is a ternary active component composed of molybdenum or tungsten and cobalt and nickel. Although the catalyst has good low-temperature activity, it is not suitable for treating oxygen-containing Claus tail gas, and there is no mention of catalytic CO conversion function.
[0006] A Chinese patent application with publication number CN1268719C discloses a method for preparing a Claus tail gas hydrogenation catalyst, wherein the catalyst carrier is a silicon oxide modified alumina carrier, and the active components are cobalt and molybdenum. The catalyst is first prepared into a stable solution with a stabilizer, and then extruded into strips by a kneading method. The catalyst has high organic sulfur hydrogenolysis activity and CS2 and COS hydrolysis activity, good stability, but poor antioxidant ability, and does not mention the catalytic CO conversion function.
[0007] In summary, the current Claus tail gas hydrogenation catalyst cannot have the multifunctionality of catalyzing sulfur dioxide hydrogenation, organic sulfur hydrolysis and CO conversion.
[0008] In view of this, the present invention is proposed. Summary of the invention
[0009] The present invention improves the low-temperature catalytic activity of the catalyst by adding a low-temperature active component, and improves the antioxidant capacity of the catalyst by adding an antioxidant. The catalyst has the characteristics of high low-temperature activity and strong antioxidant capacity, as well as multifunctional catalytic properties of catalyzing sulfur dioxide hydrogenation, organic sulfur hydrolysis, and CO conversion (CO is converted into CO2). The catalyst can be widely used in Claus tail gas hydrogenation reactors of sulfur recovery devices in petroleum refining and coal chemical industries, and has a better catalytic effect on acidic gases with a high CO2 content.
[0010] One of the objectives of the present invention is to provide a Claus tail gas hydrogenation catalyst.
[0011] A second object of the present invention is to provide a method for preparing the Claus tail gas hydrogenation catalyst.
[0012] The third object of the present invention is to provide an application of the Claus tail gas hydrogenation catalyst.
[0013] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0014] In a first aspect, the present invention provides a Claus tail gas hydrogenation catalyst, comprising an aluminum-titanium-silicon based composite carrier and an active component.
[0015] The aluminum-titanium-silicon-based composite carrier comprises Al2O3, nano-TiO2 and SiO2, and the aluminum-titanium-silicon-based composite carrier also comprises an antioxidant.
[0016] Based on the weight of the aluminum-titanium-silicon based composite carrier, the weight percentage of Al2O3 is 47% to 88%, the weight percentage of nano-TiO2 is 10% to 40%, the weight percentage of SiO2 is 1% to 10%, and the weight percentage of the antioxidant is 1% to 3%;
[0017] The active components include oxides of Group VIII metals, oxides of Group VIB metals and oxides of rare earth metals.
[0018] Based on the weight of the Claus tail gas hydrogenation catalyst, the weight percentage of the oxide of the VIII group metal is 1% to 3%, the weight percentage of the oxide of the VIB group metal is 5% to 15%, and the weight percentage of the oxide of the rare earth metal is 5% to 10%.
[0019] 1. Carrier
[0020] The carrier of the present invention is an aluminum-titanium-silicon based composite carrier, which is mainly composed of Al2O3, nano-TiO2 and SiO2, wherein Al2O3 accounts for 47% to 88% of the weight of the carrier, such as 48%, 50%, 52%, 55%, 58%, 60%, 62%, 65%, 70%, 75%, 80%, 85%, but not limited to this; nano-TiO2 accounts for 10% to 40% of the weight of the carrier, such as 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, but not limited to this; SiO2 accounts for 1% to 10% of the weight of the carrier, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, but not limited to this.
[0021] There is no particular restriction on the source of Al2O3, and pseudo-boehmite can be used as the raw material.
[0022] There is no particular restriction on the source of nano-TiO2, which can be obtained from the market or prepared by itself. Preferably, the average particle size of nano-TiO2 is 10 to 50 nm.
[0023] There is no particular restriction on the source of SiO2, and diatomaceous earth can be used as a raw material.
[0024] During the preparation process of the carrier of the present invention, an appropriate amount of a pore expander, a binder and an antioxidant are added, and the aluminum-titanium-silicon based composite carrier is prepared by a kneading method.
[0025] In some embodiments, the antioxidant is iron oxide (Fe2O3).
[0026] The antioxidant accounts for 1% to 3% of the weight of the carrier, preferably 1%.
[0027] 2. Active ingredients
[0028] The Group VIII metal is one selected from cobalt and nickel, preferably cobalt. The salt of the Group VIII metal (cobalt) can be used as a raw material and loaded on a carrier by a solution impregnation method. For example, the cobalt salt can be any water-soluble cobalt salt such as cobalt acetate, cobalt nitrate, and cobalt chloride.
[0029] The VIB group metal is one selected from tungsten and molybdenum, preferably molybdenum. The salt or oxide of the VIB group metal (molybdenum) can be used as a raw material and loaded on a carrier by a solution impregnation method. For example, the molybdenum salt can be any water-soluble molybdenum salt such as ammonium heptamolybdate, ammonium molybdate, ammonium paramolybdate, sodium molybdate, etc., and the molybdenum oxide can be molybdenum trioxide.
[0030] The rare earth metal is one or more selected from La and Nd, preferably La and Nd. The rare earth metal is added to the carrier in the form of oxide by kneading.
[0031] Among them, the oxide of Group VIII metal (such as CoO) accounts for 1% to 3% of the weight of the catalyst, such as 1%, 2%, 3%, but not limited to this; the oxide of Group VIB metal (such as MoO3) accounts for 5% to 15% of the weight of the catalyst, such as 6%, 8%, 10%, 12%, but not limited to this; the oxide of rare earth metal (such as the sum of La and Nd oxides) accounts for 5% to 10% of the weight of the catalyst, such as 6%, 7%, 8%, 9%, but not limited to this.
[0032] In a second aspect, the present invention provides a method for preparing the Claus tail gas hydrogenation catalyst, comprising the following steps:
[0033] (1) Pseudo-boehmite, nano-TiO2, diatomaceous earth, rare earth metal oxide, pore expander, binder, antioxidant source and water are kneaded together, and then extruded, dried and calcined to prepare an aluminum-titanium-silicon-based composite carrier modified with rare earth metal oxide;
[0034] (2) A salt of a Group VIII metal, a salt or oxide of a Group VIB metal, a complexing agent and water are prepared into an impregnation solution, and an aluminum-titanium-silicon-based composite carrier modified with a rare earth metal oxide is impregnated therein, and a Claus tail gas hydrogenation catalyst is obtained after drying and calcining.
[0035] Step (1):
[0036] The carrier is prepared by extrusion molding.
[0037] In some embodiments, the specific surface area of the pseudo-boehmite is ≥ 260 m 2 / g, preferably ≥300m 2 / g.
[0038] In some embodiments, the preparation method of the nano-TiO2 is as follows:
[0039] For example,Figure 1 As shown, titanic acid is added to 98% concentrated sulfuric acid at a mass ratio of titanic acid: concentrated sulfuric acid = 1:4-6 (such as 1:5), and the mixture is heated and stirred until the titanic acid is completely dissolved, and the heating is stopped. Impurities in the solution are removed by adsorption (such as adsorption with activated carbon) and filtration (such as filtration with filter paper), and an appropriate amount of deionized water is added to dilute the solution to obtain a mixed solution, so that the concentration of titanic acid in the mixed solution is 35-600 g / L. An appropriate amount of urea is added to the solution, and heating is continued to hydrolyze the urea. The reaction is terminated after the precipitation is complete, and the precipitate is washed, dried at 110-130°C for 3-5 h, calcined at 400-700°C for 3-6 h, and ground after cooling to obtain nano-TiO2 powder with an average particle size of 10-50 nm.
[0040] In some embodiments, the oxide of the rare earth metal is one or more selected from the oxides of La and Nd, preferably La2O3 and Nd2O3 in a mass ratio of 1:1.
[0041] In some embodiments, the pore expanding agent is one or more selected from polyethylene glycol, polyethylene oxide and sesbania powder, preferably polyethylene glycol with a number average molecular weight of 200-600.
[0042] In some embodiments, the binder is one or more selected from concentrated sulfuric acid, citric acid and carboxymethyl cellulose, preferably concentrated sulfuric acid.
[0043] In some embodiments, the antioxidant source is a soluble salt of iron, such as ferrous sulfate.
[0044] In some embodiments, the calcination temperature in step (1) is 400-700° C., preferably 500° C.; and / or
[0045] The calcination time is 4 to 7 hours, preferably 5 hours.
[0046] Step (2):
[0047] The relevant descriptions of the salt of Group VIII metal, the salt of Group VIB metal or the oxide are the same as those of the first aspect.
[0048] The preparation is carried out by an impregnation method, and active components cobalt and molybdenum are loaded on a carrier by a complexing agent.
[0049] In some embodiments, the complexing agent is one or more selected from ethylene glycol, citric acid and phosphoric acid, preferably a combination of ethylene glycol and citric acid in a mass ratio of 1:1.
[0050] The catalyst was prepared by the equal volume impregnation method, specifically: the catalyst carrier was immersed in deionized water at room temperature. After soaking for a period of time, the volume of deionized water reduced, that is, the volume impregnated into the catalyst carrier, was recorded, and the same volume of impregnation liquid was used for impregnation, which is the equal volume impregnation method.
[0051] In some embodiments, the immersion time is 30 min to 3 h, preferably 1 to 2 h.
[0052] In some embodiments, the calcination temperature in step (2) is 300-500° C.; and / or
[0053] The calcination time is 2 to 6 hours.
[0054] The catalyst can be in the shape of strip, sphere, three-leaf clover, four-leaf clover, etc. Three-leaf or four-leaf clover shape.
[0055] In one embodiment of the method for preparing the Claus tail gas hydrogenation catalyst, the exemplary method is as follows: Figure 2 As shown, the following steps are included:
[0056] 1. Preparation of carrier:
[0057] Pseudo-boehmite (specific surface area ≥300m 2 / g), nano-TiO2, diatomaceous earth, rare earth metal oxides, FeSO4, pore expander, binder, and water are added to the kneading machine for kneading. After kneading, a three-leaf or four-leaf clover-shaped perforated plate with a diameter of ф3mm is used for extrusion molding, dried at 110-150℃ for 2-4h, and calcined at 400-700℃ for 4-7h to obtain an aluminum-titanium-silicon-based composite carrier modified with rare earth metal oxides. The specific surface area of the carrier is measured by N2 adsorption method, which should be greater than 260m 2 / g.
[0058] 2. Preparation of Catalyst
[0059] Ammonium heptamolybdate and cobalt nitrate are added to deionized water and stirred until completely dissolved to prepare a mixed solution. A complexing agent is added to deionized water to prepare a complexing solution. The two solutions are mixed and fixed to volume to prepare an active component impregnation solution. A certain amount of the impregnation solution is taken and the carrier of step 1 is impregnated at room temperature for 1 to 2 hours, dried at 110 to 150° C. for 2 to 6 hours, and calcined at 300 to 500° C. for 2 to 6 hours to obtain the catalyst of the present invention.
[0060] The rare earth metals in the active components of the catalyst are added to the aluminum-titanium-silicon based composite carrier in the form of oxides by a kneading method, the active components cobalt and molybdenum are loaded on the carrier by an impregnation method, the antioxidant Fe2O3 is added to the carrier in the form of FeSO4, MoO3 is added in the form of molybdenum trioxide or ammonium heptamolybdate, CoO is added in the form of cobalt carbonate or cobalt nitrate, and the rare earth metals are added in the form of La2O3 and Nd2O3. In the obtained catalyst, the content of rare earth metal oxides is 5-10%, the content of MoO3 is 5-15%, and the content of CoO is 1-3%, based on the weight of the catalyst.
[0061] In a third aspect, the present invention provides an application of the Claus tail gas hydrogenation catalyst in sulfur recovery tail gas treatment.
[0062] The catalyst of the present invention can be widely used in hydrogenation reactors in sulfur recovery tail gas treatment devices in industries such as petroleum refining and coal chemical industry, and is particularly suitable for treating acid gas with a high CO2 content.
[0063] Beneficial effects:
[0064] The carrier of the catalyst prepared by the present invention is an aluminum-titanium-silicon-based composite carrier, in which the titanium component is added using nano-scale TiO2 particles. Compared with the commonly used industrial-grade TiO2, nano-scale TiO2 can more effectively improve the catalytic performance of the catalyst. The average particle size of industrial-grade TiO2 is generally 200-300nm, while the average particle size of nano-scale TiO2 particles is only 10-50nm. The carrier prepared using nano-scale TiO2 particles has a smaller pore size and is easier to adsorb sulfur dioxide, carbon disulfide, carbonyl sulfide and Sx in Claus tail gas, and has higher adsorption performance; and compared with the commonly used industrial-grade TiO2, nano-scale TiO2 is not easy to form water droplets on the carrier surface, which effectively prevents the inhibition of catalyst performance by water droplets.
[0065] By adding low-temperature catalytic active components during the preparation process, the catalyst can have the functions of catalyzing sulfur dioxide hydrogenation, organic sulfur hydrolysis and CO conversion under low-temperature conditions. By adding active component rare earth metals, the catalytic activity and thermal stability of the catalyst are improved. By adding antioxidants to the carrier, the antioxidant ability of the catalyst is improved. The catalyst can be used in the hydrogenation reactor of the sulfur recovery unit, and is suitable for the treatment of acid gas with high CO2 content in industries such as petroleum refining and coal chemical industry, effectively reducing the SO2 and CO content in the exhaust gas, meeting the current national environmental protection emission standards, and having significant economic and social benefits.
[0066] The present invention has been described in detail above, but the above embodiments are only illustrative in nature and are not intended to limit the present invention. In addition, this article is not limited by any theory described in the above prior art or invention content or the following examples. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] Figure 1 The present invention is a flow chart of the preparation of nano-TiO2 according to one embodiment of the present invention.
[0068] Figure 2 The present invention is a flow chart of the preparation of a Claus tail gas hydrogenation catalyst according to an embodiment of the present invention.
[0069] Figure 3 This is a schematic diagram of a sulfur micro-reactor evaluation device in the catalyst activity evaluation of an embodiment of the present invention;
[0070] In the figure: 1-hydrogen; 2-oxygen; 3-hydrogen sulfide; 4-sulfur dioxide; 5-nitrogen; 6-carbon disulfide; 7-carbon monoxide; 8-water; 9-mass flow meter; 10-mixing tank; 11-reactor; 12-sulfur accumulator; 13-cold trap; 14-water pump; 15-automatic control system; 16-alkali solution tank; 17-exhaust gas exhaust. DETAILED DESCRIPTION
[0071] The present invention is further described below in conjunction with examples. It should be noted that the following examples are provided for illustrative purposes only and do not constitute a limitation on the scope of protection claimed for the present invention.
[0072] Unless otherwise specified, the raw materials, reagents, methods, etc. used in the examples are conventional raw materials, reagents, methods in the art.
[0073] Example
[0074] Embodiment 1:
[0075] Add titanic acid to 98% concentrated sulfuric acid at a mass ratio of titanic acid: concentrated sulfuric acid = 1:5, heat and stir until the titanic acid is completely dissolved, stop heating, add appropriate amount of deionized water to dilute to obtain a mixed solution, make the concentration of titanic acid in the mixed solution 300g / L, add appropriate amount of urea to the solution until the pH value of the solution is 8.5-9.0, continue heating to hydrolyze the urea, terminate the reaction after complete precipitation, wash the precipitate, dry at 120°C for 4h, calcine at 500°C for 5h, and grind after cooling to obtain nano TiO2 powder with a particle size distribution between 10 and 20nm.
[0076] Take 218g of pseudo-boehmite (specific surface area of 300m 2 / g), 20g diatomaceous earth, 51g nano-TiO2 powder, 9g lanthanum trioxide, 9g neodymium trioxide, 5g sesbania powder, 30g concentrated sulfuric acid, and 4.7g ferrous sulfate were dissolved in 275ml deionized water and mixed evenly, extruded on an extruder, dried at 130°C for 4h, and calcined at 500°C for 5h to obtain an aluminum-titanium-silicon-based composite carrier modified by La2O3 and Nd2O3.
[0077] Take 6 ml of citric acid in 100 ml of deionized water, mix 14.7 g of cobalt nitrate and 30 g of molybdenum trioxide, add to the aqueous solution containing citric acid, stir until completely dissolved, and obtain the active component impregnation solution after constant volume. The carrier is impregnated with the impregnation solution for 2 hours, dried at 130°C for 2 hours, and calcined at 500°C for 5 hours to obtain a catalyst. The content of rare earth metal oxide in the catalyst thus obtained accounts for 6% of the catalyst mass, the content of MoO3 accounts for 10% of the catalyst mass, and the content of CoO accounts for 2% of the catalyst mass.
[0078] Comparative Example 1: Compared with Example 1, the ferrous sulfate in Example 1 is removed.
[0079] Comparative Example 2: Compared with Example 1, the ferrous sulfate in Example 1 is replaced with 5.17 g of manganese sulfate (which exists in the carrier in the form of MnO after roasting).
[0080] Comparative Example 3: Compared with Example 1, the nano-TiO2 powder in Example 1 is removed.
[0081] Comparative Example 4: Compared with Example 1, the nano-TiO2 powder in Example 1 was replaced with industrial TiO2 powder (purchased from Feiran Chemical Co., Ltd., Zibo City, Shandong Province, R-618).
[0082] Comparative Example 5: Compared with Example 1, the nano-TiO2 in Example 1 is replaced with TiO2 powder obtained by directly calcining titanic acid at 500°C.
[0083] Comparative Example 6: Compared with Example 1, the concentration of titanic acid in the nano-TiO2 preparation method in Example 1 is changed to 10 g / L.
[0084] Comparative Example 7: Compared with Example 1, the calcination temperature of nano-TiO2 in Example 1 is changed to 350°C.
[0085] Embodiment 2:
[0086] Add titanic acid to 98% concentrated sulfuric acid at a mass ratio of titanic acid: concentrated sulfuric acid = 1:5, heat and stir until the titanic acid is completely dissolved, stop heating, add appropriate amount of deionized water to dilute to obtain a mixed solution, make the concentration of titanic acid in the mixed solution 50g / L, add appropriate amount of urea to the solution until the pH value of the solution is 8.5-9.0, continue heating to hydrolyze the urea, terminate the reaction after complete precipitation, wash the precipitate, dry at 110°C for 5h, calcine at 400°C for 4h, and grind after cooling to obtain nano TiO2 powder.
[0087] Take 186g of pseudo-boehmite (specific surface area of 300m 2 / g), 20g diatomaceous earth, 43g nano-TiO2 powder, 15g lanthanum trioxide, 15g neodymium trioxide, 5g sesbania powder, 30g concentrated sulfuric acid, and 10.5g ferrous sulfate were dissolved in 275ml deionized water and mixed evenly, extruded on an extruder, dried at 130°C for 4h, and calcined at 500°C for 5h to obtain an aluminum-titanium-silicon-based composite carrier modified by La2O3 and Nd2O3.
[0088] Take 6 ml of citric acid in 100 ml of deionized water, mix 22.1 g of cobalt nitrate and 45 g of molybdenum trioxide, add to the aqueous solution containing sulfuric acid, stir until completely dissolved, and obtain the active component impregnation solution after constant volume. The carrier is impregnated with the impregnation solution for 2 hours, dried at 130°C for 2 hours, and calcined at 400°C for 5 hours to obtain a catalyst. The content of rare earth metal oxide in the catalyst thus obtained accounts for 10% of the catalyst mass, the content of MoO3 accounts for 15% of the catalyst mass, and the content of CoO accounts for 3% of the catalyst mass.
[0089] Comparative Example 8: Compared with Example 2, the cobalt nitrate in Example 2 was removed.
[0090] Comparative Example 9: Compared with Example 2, the molybdenum trioxide in Example 2 is removed.
[0091] Embodiment 3:
[0092] Add titanic acid to 98% concentrated sulfuric acid at a mass ratio of titanic acid: concentrated sulfuric acid = 1:5, heat and stir until the titanic acid is completely dissolved, stop heating, add appropriate amount of deionized water to dilute to obtain a mixed solution, so that the concentration of titanic acid in the mixed solution is 300 g / L, add appropriate amount of urea to the solution until the pH value of the solution is 8.5-9.0, continue heating to hydrolyze the urea, terminate the reaction after complete precipitation, wash the precipitate, dry at 120°C for 4h, calcine at 500°C for 5h, and grind after cooling to obtain nano TiO2 powder.
[0093] Take 218g of pseudo-boehmite (specific surface area of 300m 2 / g), 20g diatomaceous earth, 47.5g nano-TiO2 powder, 7.5g lanthanum trioxide, 7.5g neodymium trioxide, 5g sesbania powder, 30g concentrated sulfuric acid, and 4.6g ferrous sulfate were dissolved in 275ml deionized water and mixed evenly, extruded on an extruder, dried at 130°C for 4h, and calcined at 500°C for 5h to obtain an aluminum-titanium-silicon-based composite carrier modified by La2O3 and Nd2O3.
[0094] Take 6 ml of citric acid in 100 ml of deionized water, mix 7.4 g of cobalt nitrate and 39 g of molybdenum trioxide evenly, add to the aqueous solution containing sulfuric acid, stir until completely dissolved, and obtain the active component impregnation solution after constant volume. The carrier is impregnated with the impregnation solution for 2 hours, dried at 130°C for 2 hours, and calcined at 500°C for 7 hours to obtain a catalyst. The content of rare earth metal oxide in the catalyst thus obtained accounts for 5% of the catalyst mass, the content of MoO3 accounts for 13% of the catalyst mass, and the content of CoO accounts for 1% of the catalyst mass.
[0095] Comparative Example 10: Compared with Example 3, the lanthanum trioxide and neodymium trioxide in Example 3 are removed.
[0096] Comparative Example 11: Compared with Example 3, the lanthanum trioxide and neodymium trioxide in Example 3 are replaced with lanthanum trioxide of equal mass.
[0097] Embodiment 4:
[0098] Add titanic acid to 98% concentrated sulfuric acid at a mass ratio of titanic acid: concentrated sulfuric acid = 1:5, heat and stir until the titanic acid is completely dissolved, stop heating, add appropriate amount of deionized water to dilute to obtain a mixed solution, so that the concentration of titanic acid in the mixed solution is 300 g / L, add appropriate amount of urea to the solution until the pH value of the solution is 8.5-9.0, continue heating to hydrolyze the urea, terminate the reaction after complete precipitation, wash the precipitate, dry at 120°C for 4h, calcine at 500°C for 5h, and grind after cooling to obtain nano TiO2 powder.
[0099] Take 220g of pseudo-boehmite (specific surface area of 300m 2 / g), 20g diatomaceous earth, 50g nano-TiO2 powder, 12g lanthanum trioxide, 12g neodymium trioxide, 5g sesbania powder, 30g concentrated sulfuric acid, and 4.8g ferrous sulfate were dissolved in 275ml deionized water and mixed evenly, extruded on an extruder, dried at 130°C for 4h, and calcined at 500°C for 5h to obtain an aluminum-titanium-silicon-based composite carrier modified by La2O3 and Nd2O3.
[0100] Take 6 ml of citric acid in 100 ml of deionized water, mix 7.4 g of cobalt nitrate and 24 g of molybdenum trioxide evenly, add to the aqueous solution containing sulfuric acid, stir until completely dissolved, and obtain the active component impregnation solution after constant volume. The carrier is impregnated with the impregnation solution for 2 hours, dried at 130°C for 2 hours, and calcined at 500°C for 6 hours to obtain a catalyst. The content of rare earth metal oxide in the catalyst thus obtained accounts for 8% of the catalyst mass, the content of MoO3 accounts for 8% of the catalyst mass, and the content of CoO accounts for 1% of the catalyst mass.
[0101] Embodiment 5:
[0102] Add titanic acid to 98% concentrated sulfuric acid at a mass ratio of titanic acid: concentrated sulfuric acid = 1:5, heat and stir until the titanic acid is completely dissolved, stop heating, add appropriate amount of deionized water to dilute to obtain a mixed solution, so that the concentration of titanic acid in the mixed solution is 300 g / L, add appropriate amount of urea to the solution until the pH value of the solution is 8.5-9.0, continue heating to hydrolyze the urea, terminate the reaction after complete precipitation, wash the precipitate, dry at 120°C for 4h, calcine at 500°C for 5h, and grind after cooling to obtain nano-particle TiO2 powder.
[0103] Take 220g of pseudo-boehmite (specific surface area of 300m 2 / g), 20g diatomaceous earth, 45g nano-TiO2 powder, 10.5g lanthanum trioxide, 10.5g neodymium trioxide, 5g sesbania powder, 30g concentrated sulfuric acid, and 4.6g ferrous sulfate were dissolved in 275ml deionized water and mixed evenly, extruded on an extruder, dried at 130°C for 4h, and calcined at 500°C for 5h to obtain an aluminum-titanium-silicon-based composite carrier modified by La2O3 and Nd2O3.
[0104] Take 6 ml of citric acid in 100 ml of deionized water, mix 14.7 g of cobalt nitrate and 33 g of molybdenum trioxide evenly, add to the aqueous solution containing sulfuric acid, stir until completely dissolved, and obtain the active component impregnation solution after constant volume. The carrier is impregnated with the impregnation solution for 2 hours, dried at 130°C for 2 hours, and calcined at 700°C for 6 hours to obtain a catalyst. The content of rare earth metal oxide in the catalyst thus obtained accounts for 7% of the catalyst mass, the content of MoO3 accounts for 11% of the catalyst mass, and the content of CoO accounts for 2% of the catalyst mass.
[0105] Embodiment 6:
[0106] Add titanic acid to 98% concentrated sulfuric acid at a mass ratio of titanic acid: concentrated sulfuric acid = 1:5, heat and stir until the titanic acid is completely dissolved, stop heating, add appropriate amount of deionized water to dilute to obtain a mixed solution, so that the concentration of titanic acid in the mixed solution is 300 g / L, add appropriate amount of urea to the solution until the pH value of the solution is 8.5-9.0, continue heating to hydrolyze the urea, terminate the reaction after complete precipitation, wash the precipitate, dry at 120°C for 4h, calcine at 500°C for 5h, and grind after cooling to obtain nano TiO2 powder.
[0107] Take 225g of pseudo-boehmite (specific surface area of 300m 2 / g), 20g diatomaceous earth, 49g nano TiO2 powder, 13.5g lanthanum trioxide, 13.5g neodymium trioxide, 5g sesbania powder, 30g concentrated sulfuric acid, 4.8g ferrous sulfate is dissolved in 275ml deionized water and mixed evenly, extruded on an extruder, dried at 130°C for 4h, and calcined at 500°C for 5h to obtain La2O3 and Nd2O3 modified aluminum-titanium-silicon based composite carrier.
[0108] Take 6 ml of citric acid in 100 ml of deionized water, mix 22.1 g of cobalt nitrate and 15 g of molybdenum trioxide, add to the aqueous solution containing sulfuric acid, stir until completely dissolved, and obtain the active component impregnation solution after constant volume. The carrier is impregnated with the impregnation solution for 2 hours, dried at 130°C for 2 hours, and calcined at 450°C for 5 hours to obtain a catalyst. The content of rare earth metal oxide in the catalyst thus obtained accounts for 9% of the catalyst mass, the content of MoO3 accounts for 5% of the catalyst mass, and the content of CoO accounts for 3% of the catalyst mass.
[0109] Table 1 shows the content of active ingredients in each example.
[0110] Table 1 Example active component content
[0111]
[0112] Performance Testing
[0113] According to GB-T34233-2017 low temperature sulfur tail gas hydrogenation catalyst activity test method, in the sulfur micro-reactor evaluation device (such as Figure 3 The activity of the catalysts prepared in Examples 1 to 6 and Comparative Examples 1 to 11 was evaluated as shown above. The reactor of the microreactor was made of a stainless steel tube with an inner diameter of 20 mm and heated in a thermostat. The catalyst loading was 10 ml, and quartz sand of the same particle size was loaded on the top for mixing and preheating. The reaction gas volume composition was H2S1%, SO2 0.6%, CS2 0.6%, H210%, water 30%, O2 0.02-1%, CO 0.02-3% and the rest was nitrogen. The reaction conditions were a volume space velocity of 1200 h -11 , reaction temperature 200℃, pressure 0.1MPa.
[0114] The SO2 hydrogenation conversion rate of the catalyst was calculated according to the following formula:
[0115]
[0116] Where: M0 and M1 represent the volume concentration of SO2 at the reactor inlet and outlet respectively.
[0117] The organic sulfur hydrolysis rate of the catalyst was calculated according to the following formula:
[0118]
[0119] Where: C0 and C1 are the volume concentrations of CS2 at the reactor inlet and outlet, respectively.
[0120] The CO conversion rate of the catalyst was calculated according to the following formula:
[0121]
[0122] Where: N0 and N1 represent the volume concentration of CO at the reactor inlet and outlet, respectively.
[0123] The above method was used to evaluate the activity of the catalysts prepared in Examples 1 to 6 and Comparative Examples 1 to 11. The evaluation results are shown in Table 2.
[0124] Table 2 Catalyst activity evaluation results
[0125]
[0126] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents, without departing from the spirit and essence of the claims of the present invention; and these modifications or replacements are still within the scope defined by the claims of the present invention.
Claims
1. A Claus tail gas hydrogenation catalyst, characterized in that: It includes an aluminum-titanium-silicon based composite carrier and an active component. The aluminum-titanium-silicon-based composite carrier comprises Al2O3, nano-TiO2 and SiO2, and the aluminum-titanium-silicon-based composite carrier also comprises an antioxidant. Based on the weight of the aluminum-titanium-silicon based composite carrier, the weight percentage of Al2O3 is 47% to 88%, the weight percentage of nano-TiO2 is 10% to 40%, the weight percentage of SiO2 is 1% to 10%, and the weight percentage of the antioxidant is 1% to 3%; The active components include oxides of Group VIII metals, oxides of Group VIB metals and oxides of rare earth metals. Based on the weight of the Claus tail gas hydrogenation catalyst, the weight percentage of the oxide of the VIII group metal is 1% to 3%, the weight percentage of the oxide of the VIB group metal is 5% to 15%, and the weight percentage of the oxide of the rare earth metal is 5% to 10%.
2. The Claus tail gas hydrogenation catalyst according to claim 1, characterized in that: The average particle size of the nano-TiO2 is 10-50 nm.
3. The Claus tail gas hydrogenation catalyst according to claim 1, characterized in that: The antioxidant is iron oxide.
4. The Claus tail gas hydrogenation catalyst according to claim 1, characterized in that: The Group VIII metal is one selected from cobalt and nickel, preferably cobalt; and / or The VIB group metal is one selected from tungsten and molybdenum, preferably molybdenum; and / or The rare earth metal is one or more selected from La and Nd, preferably La and Nd.
5. The method for preparing the Claus tail gas hydrogenation catalyst according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Pseudo-boehmite, nano-TiO2, diatomaceous earth, rare earth metal oxide, pore expander, binder, antioxidant source and water are kneaded together, and then extruded, dried and calcined to prepare an aluminum-titanium-silicon-based composite carrier modified with rare earth metal oxide; (2) A salt of a Group VIII metal, a salt or oxide of a Group VIB metal, a complexing agent and water are prepared into an impregnation solution, and an aluminum-titanium-silicon-based composite carrier modified with a rare earth metal oxide is impregnated therein, and a Claus tail gas hydrogenation catalyst is obtained after drying and calcining.
6. The preparation method according to claim 5, characterized in that: The preparation method of the nano-TiO2 is as follows: Add titanic acid to concentrated sulfuric acid at a mass ratio of titanic acid: concentrated sulfuric acid = 1:4-6, heat and stir until the titanic acid is completely dissolved, stop heating, add water to dilute to obtain a mixed solution, and make the concentration of titanic acid in the mixed solution 35-600 g / L, add an appropriate amount of urea to the solution, continue heating to hydrolyze the urea, terminate the reaction after complete precipitation, wash the precipitate, dry at 110-130°C for 3-5 hours, calcine at 400-700°C for 3-6 hours, and grind after cooling to obtain nano TiO2 powder with an average particle size of 10-50 nm.
7. The preparation method according to claim 5, characterized in that: The rare earth metal oxide in step (1) is one or more oxides selected from La and Nd, preferably La2O3 and Nd2O3 in a mass ratio of 1:1; and / or The pore-enlarging agent is one or more selected from polyethylene glycol, polyethylene oxide and sesbania powder, preferably polyethylene glycol with a number average molecular weight of 200 to 600; and / or The binder is one or more selected from concentrated sulfuric acid, citric acid and carboxymethyl cellulose, preferably concentrated sulfuric acid; and / or Sources of antioxidants are soluble salts of iron.
8. The preparation method according to claim 5, characterized in that: The calcination temperature of step (1) is 400-700°C, preferably 500°C; and / or The calcination time is 4 to 7 hours, preferably 5 hours.
9. The preparation method according to claim 5, characterized in that: The immersion time of step (2) is 30 min to 3 h, preferably 1 to 2 h; The calcination temperature of step (2) is 300-500° C.; and / or The calcination time is 2 to 6 hours.
10. Use of the Claus tail gas hydrogenation catalyst according to any one of claims 1 to 4 in sulfur recovery tail gas treatment.
Citation Information
Patent Citations
Low-temperature Claus tail-gas hydrogenation catalyst and preparation method thereof
CN101879451A
Preparation method of hydrodesulfurization catalyst for high-nitrogen low-quality gasoline and diesel
CN102151582A
Sulfur dioxide selective hydrogenation sulfur preparation catalyst and preparation method thereof
CN110548517A
Multifunctional sulfur reco catalyst and preparation method thereof
CN111068746A
Catalyst compositions based on nanoparticles of a zirconium oxide, a titanium oxide or a mixed zirconium / titanium oxide deposited onto an alumina or aluminum oxyhydroxide support therefor
US20110053763A1
Cited By
Acid gas sulfur recovery process with low sulfur emission
CN121800145A
Low sulfur emission acid gas sulfur recovery process
CN121800145B
Sulfur recovery catalyst and preparation method thereof
CN122076448A